ANALISIS PENGARUH OPINI AUDIT TERHADAP PERGERAKAN HARGA SAHAM DENGAN REPUTASI AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Farah Fadhilah; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This research aims to analyze the influence of audit opinions on stock price movement with the auditor’s reputation as a moderation variable. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange from 2018 to 2020. Based on the sampling process, the total sample used in the study amounted to 119 companies. The analysis of data was done by using SPSS 23 software. Data analysisconsist of several processes, namely descriptive analysis, classical assumption tests, and multiple linear regression analysis. Based on the result of the analysis, it shows that the audit opinion positively affects the stock price movement by controlled by return on asset, leverage, and current year losses in addition, this study also proves that the raputation of auditor can not moderate the relationship between audit opinion and stock price movement.